Internal Diameter of the Main Pancreatic Duct A Post Mortem Study - Shahriah, Sunjida; Ahmed, Md Shameem; Alam, Md Jahangir; Rayhan, Khandaker Abu; Nurunnabi, Abu Sadat Mohammad; Begum, Gul Newaz; Ahmed, Rukshana; Ara, Shamim (Bangladesh Journal of Anatomy, 2010)
Context: Main pancreatic duct is an important vessel for transport of pancreatic exocrine secretion. It gradually tapers towards the tail. Progressive narrowing of the internal diameter of the main pancreatic duct is dangerous for removal of pancreatic or dislodged gallbladder calculi. Study design: A descriptive type of study. Place and period of study: The study was carried out in the Department of Anatomy, Dhaka Medical College, from August 2005 to December 2006. Materials: The present study was performed on 75 male humans. The samples were collected from the unclaimed dead bodies within 24 hours after death that were under examination in the Department of Forensic Medicine of Dhaka Medical College, Dhaka. Method: The samples were divided into 7 different age groups and comparative studies were made between different groups. All samples were studied morphologically. Internal diameter of the main pancreatic duct was measured at four points with the help of a dissecting microscope. Result: Internal diameter of the main pancreatic duct increased progressively with age, which showed positive correlation and was statistically significant (P<0.001). Conclusion: Further studies with large sample in both sexes, comparison of internal diameter of main pancreatic duct with in situ X-ray, corrosion cast of the pancreatic ductal system, pancreatic ductal histological studies are recommended. Key words: Main pancreatic duct; internal diameter. DOI: 10.3329/bja.v7i2.6098 Bangladesh Journal of Anatomy July 2009, Vol. 7 No. 2 pp. 109-116